Die neue Europäische Staatsanwaltschaft Bedeutung, Herausforderungen und erste Erfahrungen - Niedernhuber, Tanja (Schriften zum Internationalen und Europäischen Strafrecht, 2023)
With the establishment of the European Public Prosecutor's Office (EPPO), a quantum leap in cross-border criminal prosecution in Europe has been achieved. One year after the start of operational activities, a conference took place at the University of Munich, which was dedicated to initial experiences, practical problems as well as unresolved scientific questions in connection with the EPPO. The contributions in the accompanying conference proceedings concern the practice of cross-border criminal proceedings, questions of jurisdiction in investigative proceedings, cooperation with national investigative authorities, gathering and utilisation of evidence, as well as the transnationality of criminal prosecution as a challenge for criminal defence.